Gender-responsive breeding and product profiles - Developing gender-responsive plant and animal breeding programs: principles, methods and tools - Tufan, Hale Ann (Cornell University, 2019)
Presented by Hale Ann Tufan (Cornell University), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.